Xanthogranulomatous cholecystitis in a patient with ulcerative colitis and primary sclerosing cholangitis: A case report - Mohammad Kazem Tarzamni, MD; Homa Aminzadeh Ghavifekr, MD; Hadise Zeynalkhani, MD; Masoud Shirmohamadi, MD; Elham Eghbali, MD; Ali Jafarizadeh, MD, MPH; Seyed Siavash Ghareghoran, MD; Seyedeh Elnaz Hashemizadeh, MD; Masih Falahatian, MD (Radiology Case Reports, 2023)
Chronic gallbladder disease due to xanthogranulomatous cholecystitis is uncommon, and its symptoms are generally vague. While there is no firm evidence to link xanthogranulomatous cholecystitis to primary sclerosing cholangitis or ulcerative colitis.The patient is a 41-year-old male with a history of ulcerative colitis, primary sclerosing cholangitis, and biliary stenting who complained of symptoms of anorexia, jaundice, and pruritus. In the initial ultrasound exam, there was evidence of intrahepatic and extra-hepatic bile duct dilation along with a significant and mass-like circumferential thickening of the gallbladder wall. Magnetic resonance cholangiopancreatography was performed for further evaluation, which indicated increased gallbladder wall thickness, containing multiple T2 hyper-signal nodules while the mucosal layer was intact. There was also a filling defect in the common bile duct's distal portion. These findings matched a xanthogranulomatous cholecystitis diagnosis and a possibly malignant lesion in the distal of the common bile duct. The patient ultimately had a cholecystectomy, and pathology findings confirmed the diagnosis of xanthogranulomatous cholecystitis. Biopsy specimens obtained from the distal of the common bile duct lesion were microscopically identified as intramucosal adenocarcinoma.In patients with a history of primary sclerosing cholangitis who present with nonspecific symptoms suggesting chronic gallbladder disease and radiologic evidence of circumferential gallbladder wall thickening containing intramural nodules and intact mucosa, xanthogranulomatous cholecystitis should be kept in mind.